On the Stratigraphic Positionof Pithecantropus Mandible- C. - S. Sartono (Institute for Research and Community Services (LPPM) ITB, 1970)
Abstract. Up to now almost all of Java's Early as well as Middle Pliestocene hominids are surface finds. As a result, the relative age of determinations of these specimens are matters of speculations. Pithecantropus C is also a surface find and obtained from the surface of the Lower Pleistocene Putjangan beds from the Sangiran area (Central Java, Indonesia). Within the encrusting matrix of the Pithecantropus mandible have been collected a fauna of smaller foraminifera. Based on comparison of this faunal assemblage with the faunal associations of small foraminifera from the Putjangan beds, the stratigraphic position of the mandible can be established and in this way its relative age is supposed to be Late Lower Pleistocene. Ringkasan. Hampir semua fosil-fosil hominidae berumur Plestosen Bawah dan Plestosen Tengah dipula Djawa merupaka penemuan-penemuan dipermukaan tanah. Hal ini menjebabkan penentuan umur relatip fosil-fosil itu suatu hal jang spekulatip. Pithecanthropus C merupakan pula suatu penemuan diatas permukaan tanah dari lapisan-lapisan Putjangan diderah Sangiran (Djawa Tengah, Indonesia) jang berumur Plestosen Bawah. Didalam batuan jang melekat pada rahang bawah Pithecanthropus itu terdapat fauna foraminifera ketjil. Berdasarkan perbandingan antara fauna foraminifera ketjil ini dengan fauna foraminifer ketjil jang terdapat didalam lapisan-lapisan Putjangan diatas, maka dapatlah ditentukan posisi stratigrafi rahang bawah itu didalam lapisan-lapisan Putjangan tersebut, sehingga dengan demikian dapat diperkirakan bahwa umur relatip Pithecanthropus C itu adalah Plestosen Bawah Muda.